Optimasi Waktu Kontak dan Kecepatan Pengadukan untuk Penyerapan Ion Cu(II) oleh Biosorben Kulit Matoa-CTAB - Meissa Lifangrha Ronald; Desy Kurniawati; Melindra Mulia (Lembaga Yasin AlSys, 2025)
Industrial waste containing heavy metal ions such as Cu(II) is a major cause of environmental pollution, posing serious risks to human health and ecosystem sustainability. Cu(II) ions are toxic and can lead to neurological disorders, anemia, liver and kidney damage, and even death upon excessive exposure. To address this issue, an efficient, economical, and environmentally friendly method is needed. This study aims to evaluate the ability of matoa peel as a biosorbent for Cu(II) ion removal and to analyze the effect of surface modification using the cationic surfactant Cetyltrimethylammonium Bromide (CTAB). Matoa peel was selected due to its status as agricultural waste rich in active compounds such as flavonoids, tannins, lignin, and cellulose, which contain functional groups effective in binding metal ions. CTAB modification was applied to enhance the number and strength of active adsorption sites. Characterization was conducted using Fourier Transform Infrared Spectroscopy (FTIR) to identify changes in functional groups, while adsorption tests were performed using Atomic Absorption Spectroscopy (AAS) with variations in contact time and stirring speed. The results indicated optimal conditions at 60 minutes of contact time and a stirring speed of 150 rpm, achieving a maximum adsorption capacity of 15.01 mg/g—significantly higher than that of the unmodified biosorbent. In conclusion, CTAB-modified matoa peel significantly enhances the biosorption effectiveness for Cu(II) ions. These findings support the potential use of agricultural waste as a sustainable, cost-effective biosorbent for environmentally friendly industrial wastewater treatment.